2019
DOI: 10.26434/chemrxiv.8069042.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microwave-Assisted Decarbonylation of Biomass-Derived Aldehydes Using Pd-Doped Hydrotalcites

Abstract: <p>Here we report the synthesis, characterization and activity of tunable Pd-doped hydrotalcites (Pd-HTs) for the decarbonylation of furfural, hydroxymethylfurfural (HMF), aromatic and aliphatic aldehydes under microwave conditions. The decarbonylation activity reported is a notable improvement over prior heterogeneous catalysts for this process. Furfural decarbonylation is optimized in a benign solvent compatible with biomass processing - ethanol, under relatively mild conditions and short reaction time… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Recently we reported the high activity of heterogeneous catalysts based on Pd-doped hydrotalcites (Pd-HTs) for selective decarbonylation of aldehydes. 4 In the course of this study we observed that a,b-unsaturated aldehydes decarbonylate faster than aromatic and saturated aliphatic aldehydes. Given that hydortalcites, composed of metal hydroxide sheets sandwiched by anions and water, have basic sites, they can promote aldol condensation.…”
mentioning
confidence: 66%
“…Recently we reported the high activity of heterogeneous catalysts based on Pd-doped hydrotalcites (Pd-HTs) for selective decarbonylation of aldehydes. 4 In the course of this study we observed that a,b-unsaturated aldehydes decarbonylate faster than aromatic and saturated aliphatic aldehydes. Given that hydortalcites, composed of metal hydroxide sheets sandwiched by anions and water, have basic sites, they can promote aldol condensation.…”
mentioning
confidence: 66%